Effect of using cloth menstrual pads on cognition in female athletes - Ito, S.; Kitamura, K.; Sasaki, B. (Japan Journal of Physical Education, Health and Sport Sciences, 2023)
The aim of this study was two-fold: (a) to investigate how the use of menstrual cloth pads changed the cognition and symptoms of menstruation in female athletes, and (b) to examine their effectiveness. After institutional ethical approval had been obtained, interventional research was conducted on 7 elite female athletes (age: 20.1±0.38 years) specializing in different sports, over 4 menstrual cycles. The athletes used commercially available sanitary pads in period I and disposable cloth menstrual pads in periods II to IV. The participants were asked to complete the Menstrual Distress Questionnaire (MDQ) during their menstrual period. Furthermore, on the last day of each cycle, the respondents were asked to address any issues of discomfort when using the pads. Cognitive appraisal of menstruation and menstrual symptoms (MMS) were surveyed twice: before the intervention and after period IV had ended. Cognitive appraisal did not change significantly based on mood; it depended on the athlete's anxiety trait. The results revealed that the use of menstrual cloth pads improved control of menstrual-related symptoms in daily life and practice and reduced loss of concentration. Thus, the use of menstrual cloth pads may be an effective way of conditioning the mind and body to actively engage in training and competition during the menstrual period. Previous research has suggested that menstruation is a factor that hampers the performance of female athletes. However, menstrual cloth pads may reduce the main sources of discomfort, such as pain during menstruation, reduce any negative psychological effects, and allow athletes to concentrate on training, which may result in improved performance quality. However, introspection reports suggested that some female athletes felt anxious about using menstrual cloth pads. Therefore, it is important for female athletes to explore the use of menstrual cloth pads, including their gradual introduction into daily training routines and becoming accustomed to them.